Factors influencing caregivers' uncertainty of children undergoing cardiac surgery in Bangkok, Thailand - Kunnara Maneekunwong; Arunrat Srichantaranit; Wanlaya Thampanichawat (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aims to determine the factors influencing caregivers' uncertainty about children undergoing cardiac surgery in a tertiary hospital in Bangkok, Thailand. Design/methodology/approach - A correlational predictive study was conducted among 75 caregivers of children from infancy to fifteen years old who were undergoing first time cardiac surgery in a tertiary hospital in Bangkok, Thailand. Four questionnaires were inquired to evaluate caregivers' uncertainty about the illness, and influential factors included (1) perception of the severity of the illness, (2) credible authority of health-care providers and (3) information and emotional support. The descriptive statistics, Pearson correlation coefficient and multiple regression analysis were used to analyze the data and influential factors. Findings - The significant influential factors affecting caregivers' uncertainty were (1) perception of the severity of the illness (β = 0.413, p < 0.001), (2) credible authority of health-care providers (β = −0.287, p = 0.004) and (3) information and emotional support (β = −0.223, p = 0.026), and their explanation power was about 33.9 % (R2 = 0.339, F = 13.630, p < 0.001). Research limitations/implications - A limitation of this study was that the researcher selected the sample group by convenient sampling and only caregivers of children who underwent cardiac surgery in Siriraj hospital were selected. Therefore, the sample group might have lacked variety and was not a good representative of the population. Future studies should be conducted by varying the setting and using randomized sampling. Practical implications - This study provides clear recommendations to assess the perception of the severity of the illness by caregivers, build credibility and trust by providing quality care and should develop information and emotional support interventions for reducing the levels of caregivers' uncertainty of children undergoing cardiac surgery. Originality/value - Health-care providers should develop the appropriate intervention for reducing caregivers' uncertainty by assessing the perception of the severity of the illness, providing information and emotional support and building trust for the caregivers of the children who are undergoing cardiac surgery.